TOTAL COMMUNICATION APPROACH (KOMTAL) TO IMPROVE SOCIAL INTERACTION OF DEAF CHILDREN IN ELEMENTARY CLASSES IN SPECIAL SCHOOLS - Fatima Azis (International Conference on Social and Islamic Studies, 2021)
This study aims: (1) To determine the social interaction ability of Deaf children in elementary grades inSpecial Schools before using the Total Communications approach, (2) To determine the social interaction abilities ofDeaf children in elementary grades in Special Schools after using Total Communication. The method used in thisstudy is a descriptive qualitative research method which is applied through participant observation studies to determinethe effectiveness of the Total Communication (Komtal) approach in improving the social interaction skills of deafchildren. total (Komtal) shows a lack of ability to interact socially with friends, teachers and with the surroundingenvironment. (2) After being given treatment with the total communication approach (Komtal) children with hearingimpairment in elementary grades show progress in interacting socially with the surrounding environment, but in termsof speaking, children with hearing impairments in class basis can not be categorized as perfect. Being able to speak inthe sense that deaf children can produce language sounds within certain limits. In the aural and manual components(finger spelling, natural cues, and formal cues) in general, deaf children are able to do well considering this child is achild who has abnormalities in speech and hearing organs, so that deaf children are more likely to use sign languagein communicating.